Adoption of Climate-Smart Agricultural Technologies and Practices in Fragile and Conflict-Affected Settings: A Review and Meta-Analysis - Nshakira-Rukundo, Emmanuel; Tabe-Ojong, Martin Paul; Gebrekidan, Bisrat; Agaba, Monica; Surendran Padmaja, Subash; Dhehibi, Boubaker (leibniz institute fur wirtschaftsforschung, 2025)
A major challenge for countries dealing with conflict and instability is encouraging the use of farming technologies and natural resource management practices that are climate-smart. These practices boost productivity, build resilience to climate challenges and thus contribute to other dimensions of resilience such as those associated with conflict. In this review and meta-analysis, we assess factors associated with farmers’ adoption decisions for such technologies and practices. We use advanced machine learning tools to analyze over 42,000 published papers. Focusing on countries identified as fragile due to either climate shocks or conflict, we select 109 papers and extract 1330 coefficients and implement partial correlation coefficient analysis. Our findings show that most of the research comes from two countries; Ethiopia and Nigeria and we do not find any studies from Small Island States. We categorized the technologies into five technology groups, including soil health, erosion management, mechanization, input use and risk reduction technologies. Analysis reveals that factors such as farmer training, access to information, subsidies, and past experiences of using technologies predicts further technology adoption. However, there are significant differences across various technology groups and most especially, a very low coverage of risk-reduction technologies such as insurance.